Green Marketing: Opportunities or Challenges for Micro and Small Business Actors - Siswati, Endang (The Eastasouth Management and Business, 2025)
This study is a qualitative study, which aims to analyze the perceptions of micro and small business actors towards the implementation of green marketing and identify the opportunities and challenges faced. The informants in this study were micro and small business actors in Surabaya. The data collection method was carried out directly through interviews with business owners. After the data was collected, triangulation was carried out and explained. The results of the analysis show that MSMEs are faced with an interesting dilemma in implementing environmentally friendly marketing. On the one hand, they want to contribute to environmental conservation by using environmentally friendly packaging. However, limited access to affordable environmentally friendly raw materials and the perception that such packaging will increase production costs are often barriers and will reduce profits. There are several challenges towards environmentally friendly marketing, including: environmentally friendly raw materials generally have higher prices compared to conventional raw materials, not all consumers are ready to pay more for products with environmentally friendly packaging, profit remains a top priority for some micro businesses. The opportunities include: improving brand image, opening new markets, being able to support the government and society, and encouraging MSMEs to innovate.